MultiSkipGraph: A Self-stabilizing Overlay Network that Maintains Monotonic Searchability - Luo, Linghui; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 2019 IEEE 33rd International Parallel and Distributed Processing Symposium (IPDPS '19))
Self-stabilizing overlay networks have the advantage of being able to recover from illegal states and faults. However, the majority of these networks cannot give any guarantees on their functionality while the recovery process is going on. We are especially interested in searchability, i.e., the functionality that search messages for a specific node are answered successfully if a node exists in the network. In this paper we investigate overlay networks that ensure the maintenance of monotonic searchability while the self-stabilization is going on. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We extend the existing research by focusing on skip graphs and present a solution for two scenarios: (i) the goal topology is a super graph of the perfect skip graph and (ii) the goal topology is exactly the perfect skip graph.

Debiasing Vandalism Detection Models at Wikidata - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (WWW)

A Digital Twin-Based Multi-Modal UI Adaptation Framework for Assistance Systems in Industry 4.0 - Josifovska, Klementina; Yigitbas, Enes; Engels, Gregor (Proceedings of the 21st International Conference on Human-Computer Interaction (HCII 2019))

Reference Framework for Digital Twins within Cyber-Physical Systems - Josifovska, Klementina; Yigitbas, Enes; Engels, Gregor (Proceedings of 5th International Workshop on Software Engineering for Smart Cyber-Physical Systems (SEsCPS'19))

Förderung von Kreativität in studentischen Kleingruppenprojekten in der Informatik – Ein Prototyping-basierter Ansatz - Strothmann, Thim Frederik (die hochschullehre)
Dieser Artikel erörtert, ob in studentischen Kleingruppenprojekten in der Informatik Kreativität und die Erarbeitung kreativer Ideen explizit gefördert werden kann. Dazu wird ein Seminarkonzept detailliert vorgestellt, welches auf zwei Grundkonzepten der Informatikpraxis beruht: agiles Projektvorgehen und Prototyping. Die Teilnehmenden des Seminars wurden gezielt in einen Kreativitätsprozess geleitet, indem sie für gegebene moderne Technologien (Virtual Reality, Augmented Reality, Drohnen, etc.) neuartige Nutzungsszenarien entwickeln sollten. Um zu evaluieren, ob das Lehrkonzept erfolgreich ist, wird sowohl die produktbezogene als auch die prozessbezogene Kreativität betrachtet. Für die produktbezogene Kreativität werden die von den Teilnehmenden erstellten Projektideen inklusive der benutzten Prototypingtechnik vorgestellt und bewertet. Die Teilnehmenden haben nicht nur eine enorme Breite an Ideen entwickelt (in der Summe ca. 40 bei 16 Teilnehmenden), sondern insbesondere auch acht Ideen im Verlaufe des Seminars sehr konkret weiterentwickelt. Hinsichtlich der prozessbezogenen Kreativität wird das Lehrkonzept durch mehrere Fragebögen eruiert. Die Studierenden sind mit dem Seminar, der Herangehensweise und den Ergebnissen sehr zufrieden, was unter anderem durch die äußerst positive studentische Veranstaltungskritik (u.a. 1,0 für den Gesamteindruck sowie Atmosphäre in der Veranstaltung) und die Auswertung der Evaluationsfragebögen unterstrichen wird. Auch von externen Beobachtern werden die erarbeiteten Ergebnisse und der Einsatz von Prototyping als sehr positiv bewertet.

WindCORES - Digital Transformation with Renewable Energy - Yigitbas, Enes; Schomaker, Gunnar (International Tube Association (ITAtube) Journal)

Detection and Resolution of Data-Flow Differences in Business Process Models - Jovanovikj, Ivan; Yigitbas, Enes; Gerth, Christian; Sauer, Stefan; Engels, Gregor (Information Systems Engineering in Responsible Information Systems - CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings)

Modular Construction of Context-Specific Test Case Migration Methods - Jovanovikj, Ivan; Yigitbas, Enes; Grieger, Marvin; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Consistent Runtime Adaptation of User Interfaces - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann (Proceedings of the 8th International Workshop on Bidirectional Transformations (Bx 2019))

Towards Model-based Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 21st Workshop Software-Reengineering & Evolution (WSRE) & 10th Workshop Design for Future (DFF))